2017
DOI: 10.1111/cxo.12446
|View full text |Cite
|
Sign up to set email alerts
|

The situation of low vision services in Papua New Guinea: an exploratory study

Abstract: This study has identified barriers from the perspectives of different stakeholders, including service providers and people with low vision and their families. Knowledge of these barriers can now guide the development of future low vision services in PNG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This is consistent with other studies which found transportation challenges as a common barrier to accessing services [ 14 , 16 , 27 , 28 ]. Less than one-third of the patients perceived the cost of LVR services as a barrier, a barrier relatively unique to the population of the United States and therefore addressed in a few studies [ 20 , 23 , 24 ]. Interestingly, a global survey on low-vision service provision found both cost and distance to the nearest LVR service to be more common barriers in developing countries [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with other studies which found transportation challenges as a common barrier to accessing services [ 14 , 16 , 27 , 28 ]. Less than one-third of the patients perceived the cost of LVR services as a barrier, a barrier relatively unique to the population of the United States and therefore addressed in a few studies [ 20 , 23 , 24 ]. Interestingly, a global survey on low-vision service provision found both cost and distance to the nearest LVR service to be more common barriers in developing countries [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Marella and colleagues evaluated low vision services in Papua New Guinea[27]. They described knowledge of the community and partnered with the community to explore the needs of those with low vision and the public perception of those with low vision.…”
Section: Resultsmentioning
confidence: 99%
“…Similar arrangements have been observed in most South Asian countries [ 11 ]. In other island nations, such as Papua New Guinea, refractionists and optometrists provide refraction services [ 12 ].…”
Section: Discussionmentioning
confidence: 99%